Peran Filsafat Pendidikan Islam dalam Pengelolaan Lembaga Pendidikan di SD IT Hidayatullah Yogyakarta - Muchasin, Fiki Vendi; Mujiburrohman, Mujiburrohman (TSAQOFAH, 2025)
The limited scope of existing studies on the role of Islamic educational philosophy in the management of Islamic educational institutions forms the background of this research, despite its significant impact on governance quality and educational direction. This study aims to explore the contribution of Islamic educational philosophy to management practices at SD IT Hidayatullah Yogyakarta and to identify the key challenges in its implementation. A qualitative design was employed, using purposive sampling to select eight participants, including the principal, teachers, and administrative staff. Data were collected through in-depth interviews, observation, and document analysis, and analyzed using thematic analysis techniques. The findings reveal that Islamic educational philosophy serves as a foundational framework in formulating the school’s vision and mission, strengthening religious culture, integrating the curriculum, and fostering teacher role models. However, implementation faces several obstacles, such as limited conceptual understanding among educators, a gap between ideal values and actual practices, and challenges in aligning with national curriculum requirements. The study concludes that Islamic educational philosophy plays a strategic role in shaping institutional management systems and school culture, but its successful implementation depends on strengthening human resource capacity and the ability to adapt to local contexts. These findings offer theoretical implications for the development of Islamic education management studies, as well as practical recommendations for stakeholders in designing Islamic value-based training and managerial models.